Cogito and ontology of flesh in Maurice Merleau-Ponty - Durán , David (2023)
This research focuses on how the problem of the reflexive cogito returns in Maurice Merleau-Ponty’s ontology of the flesh. In the first place, the concepts “reflexive cogito” and “tacit cogito” are developed according to Phenomenology of Perception (1945). Subsequently, the article describes the conceptual transformation of these concepts into the ones of “perceptive faith” and “reflexive philosophy” according to The Visible and the Invisible (1964). Finally, the article demonstrates how the reflexive cogito returns to the ontology of the flesh because of the priviledge given to the presence and the coincidence in the analysis of touch and vision.